2020
DOI: 10.3389/fonc.2020.548744
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of Nomograms Based on Gamma-Glutamyl Transpeptidase to Platelet Ratio for Hepatocellular Carcinoma Patients Reveal Novel Prognostic Value and the Ratio Is Negatively Correlated With P38MAPK Expression

Abstract: BackgroundEarly prediction of recurrence and death risks is significant to the treatment of hepatocellular carcinoma (HCC) patients. We aimed to develop and validate prognosis nomogram models based on the gamma-glutamyl transpeptidase (GGT)-to-platelet (PLT) ratio (GPR) for HCC and to explore the relationship between the GPR and inflammation-related signaling pathways.MethodsAll data were obtained from 2000 to 2012 in the Affiliated Hospital of Qingdao University. In the training cohort, factors included in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Liver function indexes including bilirubin, albumin, alkaline phosphatase (ALP), gamma-glutamyl transpeptidase (GGT), aspartate aminotransferase (AST) and alanine aminotransferase (ALT), are essential serum markers to determine the hepatic reserve function and feasibility of liver resection, on the basis of these indexes, several scoring systems including ALBI, FIB-4, AGR, AAPR and APRI, have been validated as efficient prognostic indicators for liver cancer patients ( 17 , 26 , 27 ). Several studies have reported that GPR demonstrated prognostic value in HCC ( 19 , 28 ); however, the predictive capability of GPR for the survival of surgically treated ICC patients is unknown. As a critical indicator of coagulation function, although INR has been proposed as a promising prognostic marker in patients with HCC and biliary tract cancer ( 21 , 29 ), its predictive effect in patients with ICC has not been studied separately.…”
Section: Discussionmentioning
confidence: 99%
“…Liver function indexes including bilirubin, albumin, alkaline phosphatase (ALP), gamma-glutamyl transpeptidase (GGT), aspartate aminotransferase (AST) and alanine aminotransferase (ALT), are essential serum markers to determine the hepatic reserve function and feasibility of liver resection, on the basis of these indexes, several scoring systems including ALBI, FIB-4, AGR, AAPR and APRI, have been validated as efficient prognostic indicators for liver cancer patients ( 17 , 26 , 27 ). Several studies have reported that GPR demonstrated prognostic value in HCC ( 19 , 28 ); however, the predictive capability of GPR for the survival of surgically treated ICC patients is unknown. As a critical indicator of coagulation function, although INR has been proposed as a promising prognostic marker in patients with HCC and biliary tract cancer ( 21 , 29 ), its predictive effect in patients with ICC has not been studied separately.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we established a nomogram relying on a combined model that can simply calculate the likelihood of VEGF status. The clinical utility of the nomogram was appraised by means of decision curve analysis ( 28 ). By measuring the disparity between the true- and false-positive rate at different thresholds, net benefits were calculated ( 29 ).…”
Section: Methodsmentioning
confidence: 99%
“…For analysis, both the staining intensity and percentage of positive tumor cells were graded and multiplied to obtain an overall staining score as described previously. 14 Staining intensity was scored on a scale of 0‐3 as follows: 0 (negative), 1 (weak), 2 (medium) and 3 (strong). Percentage of positive tumor cells was categorized into five semi-quantitative classes: 0 (≤5% positive cells), 1 (6–25% positive cells), 2 (26–50% positive cells), 3 (51–75% positive cells) and 4 (>76% positive cells).…”
Section: Methodsmentioning
confidence: 99%